Experimental Study on LTCC Glass-Ceramic Based Dual Segment Cylindrical Dielectric Resonator Antenna. (6th March 2013) - Gangwar, Ravi Kumar; Singh, S. P.; Choudhary, Meenakshi; Kumar, D.; Narayana Rao, G. Lakshmi; James Raju, K. C.
Abstract : The measured characteristics in C/X bands, including material properties of a dual segment cylindrical dielectric resonator antenna (CDRA) fabricated from glass-ceramic material based on B2 O3 –La2 O3 –MgO glass and La(Mg0.5 Ti0.5 )O3 ceramic, are reported. The sintering characteristic of the ceramic in presence of glass is determined from contact angle measurement and DTA. The return loss and input impedance versus frequency characteristics and radiation patterns of CDRA at its resonant frequency of 6.31 GHz are studied. The measured results for resonant frequency and return loss bandwidth of the CDRA are also compared with corresponding theoretical ones.